Highly Efficient Self-Healing Multifunctional Dressing with Antibacterial Activity for Sutureless Wound Closure and Infected Wound Monitoring - Tang, Ning (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2021 Wiley-VCH GmbH.